Press Release: Fitch Downgrades iHeart's IDR to 'RD' and Upgrades IDR to 'CC' on Closing of Exchange Offer (Dow Jones Institutional News, 2017)
[...]indications that a DDE is probable in the near term would also drive a downgrade. Date of Relevant Rating Committee: Feb. 8, 2017 Summary of Financial Statement Adjustments - Financial statement adjustments that depart materially from those contained in the published financial statements of the relevant rated entity or obligor are disclosed below: --Historical and projected EBITDA(R) is adjusted to add back non-cash stock-based compensation; --EBITDA(R) metrics are unadjusted for dividends received from Associates/paid to Minorities. Additional information is available at www.fitchratings.com Applicable Criteria Criteria for Rating Non-Financial Corporates (pub. 27 Sep 2016) https://www.fitchratings.com/site/re/885629 Recovery Ratings and Notching Criteria for Non-Financial Corporate Issuers (pub. 21 Nov 2016) https://www.fitchratings.com/site/re/890199 Treatment and Notching of Hybrids in Non-Financial Corporate and REIT Credit Analysis (pub. 29 Feb 2016) https://www.fitchratings.com/site/re/878264 Additional Disclosures Dodd-Frank Rating Information Disclosure Form https://www.fitchratings.com/creditdesk/press_releases/content/ridf_frame.cfm?pr_id=1018731 Solicitation Status https://www.fitchratings.com/gws/en/disclosure/solicitation?pr_id=1018731 Endorsement Policy https://www.fitchratings.com/regulatory ALL FITCH CREDIT RATINGS ARE SUBJECT TO CERTAIN LIMITATIONS AND DISCLAIMERS. The manner of Fitchâ tms factual investigation and the scope of the third-party verification it obtains will vary depending on the nature of the rated security and its issuer, the requirements and practices in the jurisdiction in which the rated security is offered and sold and/or the issuer is located, the availability and nature of relevant public information, access to the management of the issuer and its advisers, the availability of pre-existing third-party verifications such as audit reports, agreed-upon procedures letters, appraisals, actuarial reports, engineering reports, legal opinions and other reports provided by third parties, the availability of independent and...